Autograft Root Dilation After the Ross Procedure Is Not Benign. Issue 4 (July 2021) - Bichell, David P.
Autograft root dilation is common after the unsupported Ross procedure. In the absence of valvar incompetence, and with the perception that dissection is exceedingly rare, expectant management of autograft aneurysm is common practice. Autograft dissection may not be as rare as thought though, as at this point 7 case reports have accrued that describe autograft dissection requiring urgent operative intervention. All had a bicuspid native aortic valve. Bicuspid aortic valve has been shown to be associated with an intrinsic, histologically demonstrated pulmonary arteriopathy, possibly contributing to autograft root dilation and dissection. Autograft root dilation can no longer be regarded as benign, especially in patients with bicuspid aortic valve. Mounting evidence further validates the practice of externally supporting the Ross autograft. For patients who have had an unsupported Ross procedure, mounting evidence may support earlier intervention for autograft root dilation and aneurysm.